(untitled) - London, Sherry (New Jersey, 2006)
Travel to a side of Photoshop CS2 you may never have seen before! Here are nearly 50 way-out, advanced effects, colorfully illustrated step by step to show you exactly how to work the magic. Learn to handle some of Photoshop's trickiest commands, including Knockout, Blend-If, and Clipping Masks. Create glass text, submerge a city under water, create mythical creatures, cross-breed your favorite fruits — and that's just for starters. If you have experience using Photoshop, you'll love what you see on this side. Wild!
Keywords: Adobe photoshop,Computer graphics